Electrocatalytic Carbon Dioxide Reduction to Ethylene over Copper‐based Catalytic Systems. Issue 24 (8th November 2022) - Yang, Yisen; Tan, Zhonghao; Zhang, Jianling
Abstract: The electrocatalytic carbon dioxide (CO2 ) conversion to ethylene (C2 H4 ) has attracted significant attention in recent years. Copper‐based catalytic systems have been proven to be the most efficient for producing C2 H4 from electrocatalytic CO2 reduction reaction. In this review, we present the recent progress on the electrocatalytic CO2 reduction to C2 H4 over copper‐based catalytic systems, mainly focusing on reaction mechanism, design of catalysts and influences of electrolyte, CO2 supplement and electrolyzer on activity, selectivity and stability. Abstract : In this review, we present the recent progress on the electrocatalytic carbon dioxide (CO2 ) reduction to ethylene (C2 H4 ), focusing on the reaction mechanism and the effects of catalyst, electrolyte, CO2 supplement and electrolyzer on the selectivity, activity and stability of electrocatalytic CO2 ‐to‐C2 H4 conversion.